The Horizontal Curved Geometric Planning Using the Autocad® Civil 3D Method on Tanah Merah Road, Banjarbaru City, South Kalimantan - Indri Pangesti; Andri Irfan Rifai; Joewono Prasetijo (Indonesian Journal of Multidisciplinary Science, 2022)
In modern times, technological developments are very rapid, one of which is in the field of transportation, which is now a hot research topic. Transportation is closely related to safety factors, so this study discusses how to plan roads by looking at safe and comfortable design aspects. This research opens new access roads on Tanah Merah roads by concentrating on geometric horizontal arches using the AutoCAD Civil 3D® application. The writing method and research method in the preparation of this research used secondary data and qualitative research methods. The data is collected from various sources: the internet, Google Maps, Google Earth, and Global Mapping. The length of the trace along ±1,519 Km. The arch discussed in this study is the Pl4 arch with the type of Spiral Circle Spiral (S-C-S) arch. Superelevation with a radius of 300 m is 4.5%. After doing this planning, it can be concluded that using AutoCAD Civil 3D® is considered more manageable, faster, and more effective than using manual methods.